A Response to Kroeker - Baum, Gregory (Toronto journal of theology, 1986)
Travis Kroeker has written an excellent article. I am grateful for the opportunity to make a brief critical response to it. That the more recent Catholic social teaching has paid too little attention to humanity'S relation to nature is a criticism that deserves to be taken very seriously. Yet to pin the blame on the biblical injunction to subdue the earth seems superficial to me. The biblical mandate was given in an agricultural society where 'the domination' of nature aimed at the creation of a garden. In the Bible work is seen as a taming of nature. Work enhances nature in accordance with its own inclination. The domination of nature by an economic system that seeks to maximize production, profit and power, has violated the earth and transformed it into a quarry. Reflecting on the contrast between 'garden' and 'quarry' may help Christians to promote a theory and practice of labour that reconciles people with nature. In this context, increasing productivity need not mean making more commodities: it could refer to the qualitative transformation of society, human dwelling in a park.